Diferentes métodos de isolamento influenciam nas taxas de retenção do tratamento restaurador atraumático de cavidades proximais em molares deciduos? Uma revisão sistemática e meta-análise - Duda, João Gilberto (2020)
A systematic review was performed to evaluate the survival rates of minimally invasive treatment (ART) in primary molars using two methods of isolation of the operative field (rubber dam and cotton rolls). Seven databases were searched for randomized clinical trials comparing rubber dam and cotton rolls for isolation of primary cavities before ART restoration and with follow-up equal to or longer than 6 moths. The risk of bias tool from the Cochrane Collaboration was used for quality assessment of the studies. A total of 687 articles were identified. Three remained in the qualitative synthesis and all studies were considered at “unclear” risk of bias in the key domains. The studies from which the information could be extracted were included for meta-analysis. The survival rate at six-month follow-up was 1.1 (95% confidence interval [CI] = 0.85 to 1.42; p = 0.46), and the survival rate at 24 months follow-up was 1.50 (95% CI = 0.87 to 2.56; p = 0.14). None of the selected studies point out that rubber dam isolation yields a higher survival rates of Class II ART restoration; however there are few studies in the literature that compared rubber dam with cotton rolls isolation and the ones available are at “unclear” risk of bias. There is a need of further well-designed trials comparing the survival rates of ART restorations under these two isolation techniques